2004
DOI: 10.1096/fj.03-1259fje
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myocytes are a source of interleukin‐6 mRNA expression and protein release during contraction: evidence of fiber type specificity

Abstract: In this study, we aimed to determine whether skeletal muscle cells per se are a source of interleukin (IL)-6 during contraction and whether IL-6 production is fiber type specific. Muscle biopsy samples were collected from seven males before (PRE) and after (POST) completing 120 min of continuous bicycle ergometry. Biopsies were sectioned and analyzed for the following: IL-6 protein detected by immunohistochemistry (IHC), IL-6 mRNA content detected by in situ hybridization, fiber type measured by either IHC or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
2
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(196 citation statements)
references
References 21 publications
13
173
2
8
Order By: Relevance
“…IL-6 was found to be a myokine that is produced within the contracting muscle fibres [21] and released into the circulation depending on intensity and duration of exercise [22,23]. Further research revealed that IL-6 fulfils some criteria of an exercise factor, because it stimulates glucose uptake [24,25] and fatty acid oxidation in skeletal muscle [26,27], increases lipolysis [28] and activates AMP-activated protein kinase [29].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 was found to be a myokine that is produced within the contracting muscle fibres [21] and released into the circulation depending on intensity and duration of exercise [22,23]. Further research revealed that IL-6 fulfils some criteria of an exercise factor, because it stimulates glucose uptake [24,25] and fatty acid oxidation in skeletal muscle [26,27], increases lipolysis [28] and activates AMP-activated protein kinase [29].…”
Section: Discussionmentioning
confidence: 99%
“…Upon muscle contraction, IL-6 is released into the circulation the amount of which is dependent on intensity and duration of exercise [10] and the energy status of a muscle, as determined by pre-exercise glycogen content [11]. This leads to an acute increase of IL-6 plasma levels during exercise, the main sources of which are the myofibres [12].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
“…These results indicate that arm crank exercise induces changes in plasma IL-6 kinetics that are different from those of lower-body cycling exercise. Hiscock et al 20 reported that the source of IL-6 was the myocytes in exercising leg muscles at 55%VO 2 max. Therefore, we assumed the increase of IL-6 during arm exercise might come from contracting arm muscles; however, the mechanism of IL-6 production during arm crank exercise is not clear at present.…”
Section: Delayed Peak Il-6 Levelmentioning
confidence: 99%